2015
DOI: 10.1038/srep14744
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Metabolites Identify Patients with Mesangial Proliferative Glomerulonephritis, IgA Nephropathy and Normal Controls

Abstract: Urinary volatile organic compounds (VOCs) analysis for kidney diseases has attracted a large amount of scientific interest recently, and urinary metabolite analysis has already been applied to many diseases. Urine was collected from 15 mesangial proliferative glomerulonephritis (MsPGN) patients, 21 IgA nephropathy (IgAN) patients and 15 healthy controls. Solid phase microextraction–chromatography– mass spectrometry (SPME-GC-MS) was used to analyse the urinary metabolites. The statistical methods principal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Metabolomics platforms now enable the simultaneous measurement of hundreds of small molecular metabolites describing the downstream effects of genes and proteins. Patients with glomerulonephritis,7, 8, 9 kidney transplantation,10, 11 diabetes nephropathy, 12 acute kidney injury, 13 and general CKD14, 15, 16, 17 have been studied, and important disturbances in amino acid, glucose, and fatty acid metabolism as well as the central energy metabolism have been described 12, 18, 19. Whether this extends to patients with hypertensive nephrosclerosis is not well studied.…”
mentioning
confidence: 99%
“…Metabolomics platforms now enable the simultaneous measurement of hundreds of small molecular metabolites describing the downstream effects of genes and proteins. Patients with glomerulonephritis,7, 8, 9 kidney transplantation,10, 11 diabetes nephropathy, 12 acute kidney injury, 13 and general CKD14, 15, 16, 17 have been studied, and important disturbances in amino acid, glucose, and fatty acid metabolism as well as the central energy metabolism have been described 12, 18, 19. Whether this extends to patients with hypertensive nephrosclerosis is not well studied.…”
mentioning
confidence: 99%
“…44 Urinary metabolomics studies have been employed to different cancer studies, such as breast, colorectal, esophageal, pancreatic ductal adenocarcinoma, prostate, and liver cancers. 45 Analyzing four different VOCs (2,6-dimethyl-7-octen-2ol, pentanal, 3-octanone, and 2-octanone), Khalid et al demonstrated the detection of prostate cancer. 46 Matsumura et al demonstrated ex-vivo analysis of urinary VOCs as biomarkers for lung cancer.…”
Section: ■ Sources For Invasive Detectionmentioning
confidence: 99%
“…Elevated levels of acetonitrile in urine confirms whether someone is a smoker or not . Urinary metabolomics studies have been employed to different cancer studies, such as breast, colorectal, esophageal, pancreatic ductal adenocarcinoma, prostate, and liver cancers . Analyzing four different VOCs (2,6-dimethyl-7-octen-2-ol, pentanal, 3-octanone, and 2-octanone), Khalid et al demonstrated the detection of prostate cancer .…”
Section: Sources For Noninvasive Detectionmentioning
confidence: 99%
“…For example, solid-phase microextraction-chromatography-mass spectrometry (SPME-GC-MS) was used by Wang et al to study urinary volatile organic compounds, as a marker for pathological changes in the kidney. 110 Five urinary metabolites (tartronic acid, carbamic acid, sulfide, allyl methyl, hydrogen azide, and benzeneethanamine,N-[(pentafluorophenyl)methylene]-.beta.,4-bis[(trimethylsilyl)oxy]-), were identified and significantly increased in IgAN compared with MPGN patients. These results suggest urinary metabolites may be used as biomarkers to differentiate between different forms of GN.…”
Section: High-throughput Technologies In Gn Researchmentioning
confidence: 99%